Peranan Perpustakaan SMPN 15 Bandung dalam Meningkatkan Minat Baca Siswa - Sasqia Mawardah Rahmadiani; Angga Hadiapurwa (Journal on Education, 2023)
As one of source of information in schools, the library at SMPN 15 Bandung has offered various collections and facilities to meet students' information needs, but student visits to the library are still relatively low with the lack of utilization of the collections provided by students, so this article aims to find out how the role of the SMPN 15 Bandung’s library in increasing students' reading interest and what obstacles exist in the library of SMPN 15 Bandung in increasing students' reading interest. Qualitative descriptive research was used as a research method to describe the role of the SMPN 15 Bandung library in increasing students' reading interest. From the results of research conducted, increasing students' interest in reading to visit the school library has been carried out, but there are obstacles faced, such as many library collections that have not been updated, to the lack of supporting facilities for information fulfillment. For this reason, schools and libraries are advised to make various efforts, such as holding a reading corner in each class, library's club literacy day, to procurement of library ambassadors to increase library promotion as well as students' reading interest.